PEMETAAN FAKTOR-FAKTOR RISIKO SINDOROMA METABOLIK PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS TARUMANAGARA JAKARTA - Wohangara, Victor Sepriyadi; Santoso, Alexander Halim (Ebers Papyrus, 2021)
Metabolic syndrome is a group of metabolic conditions associated with central obesity, increased blood pressure, decreased glucose tolerance, insulin resistance, increased triglycerides and LDL cholesterol. In 2017, WHO stated that cardiovascular diseases (stroke, coronary heart disease), which are a manifestation of metabolic syndrome, are the number one death rate in the world. Indonesia itself has experienced an increase in the prevalence of metabolic syndrome, especially in children and adolescents, which is caused by a bad lifestyle. This study aims to identify cardiometabolic risk factors in students of the Faculty of Medicine, Universitas Tarumanagara  class of 2017. This research is descriptive with a cross-sectional design. Data were taken by interview, questionnaire, and anthropometric measurements. Data were analyzed by descriptive test. The results showed that the majority of the nutritional status of the students of the Faculty of Medicine at Tarumanagara University class of 2017 were obesity (45.2%), smoking (2.7%), not exercising (41.1%), average sleep time of 5.8 hours per day, The average screen time is seven hours per day, and 58.9% have a habit of consuming junk food once per week. Further research is needed with a more heterogeneous sample and examination of the biochemical profile to see other metabolic risk factors.